Adaptive power loading based on unequal-ber strategy for OFDM systems - Liu, Kaiming; Tang, Bihua; Liu, Yuan'an (IEEE communications letters, 2009)
An adaptive power loading algorithm with uniform (nonadaptive) bit allocation is proposed for constant data rate OFDM systems in this letter. This algorithm aims to minimize the transmit power while guaranteeing the target mean bit error rate (BER). The power loading is based on the unequal-BER (UBER) strategy which permits unequal mean BERs on different subcarriers. The closed-form expressions for optimal BER and power distributions are derived. Simulation results indicate the superiority of the proposed algorithm.